The relationship between maternal stimulation and the development of children aged 4-5 years at PAUD al Jannah Pematang Sei Baru, Asahan Regency in 2022 - Saddiyah Rangkuti (Institute of Computer Science (IOCS), 2023)
Assessment of growth and development can be done as early as possible since the child is born. Early detection is a comprehensive screening effort to find deviations in child development. Efforts that can be made for optimal motor development of children can be done by providing stimulus, improving nutritional status, APE (educational game tools) and parenting patterns (Lindawati, 2014). The purpose of this study was to determine the relationship between maternal stimulation and the development of children aged 4-5 years at PAUD Al Jannah Pematang Sei Baru, Asahan district in 2022. The type of research conducted was descriptive-analytic with a cross-sectional approach, the population in the study was 60 people using the technique accidental side. The data collected in this study is primary data, namely data obtained directly from the respondents. The data analysis used was univariate analysis and bivariate analysis. The results of the study showed that the majority of good maternal stimulation with normal child development were 23 (92%) respondents and a minority of poor maternal stimulation with abnormal child development were 1 (4%) respondents with a p value of 0.001. The calculated Chi-Square is 11,979 and the Chi-Square table for df = 1. The conclusion from this study is that there is a relationship between maternal stimulation and the development of children aged 4-5 years at PAUD Al Jannah Pematang Sei Baru, Asahan Regency in 2022. It is hoped that all education staff at PAUD Al Jannah are expected to be more active in teaching maternal stimulation of child development and providing counseling related to maternal stimulation of child development.